Effects of Long-term Antiepileptic Drugs (AED) on Serum Copper Level in Children with Epilepsy - Ahmed, Md. Ranzu; Jahan, Israt; Shamim-Ara-Sarkar; Rahman, Habibur; Sarker, Mohammad Jahangir Alam; Alam, Faridul (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
Background: Epilepsy is a central nervous system disorder in which brain activity becomes irregular, causing seizures or periods of unusual behavior, sensations, and sometimes loss of awareness. Serum copper level may change due to long-term use of antiepileptic drugs. Epilepsy is one of the most common neurological diseases with a prevalence rate varying from 2.8 to 19.5 per 1000 general population and it prevails more especially among school children. Objective: The purpose of the present study was to assess the serum copper level in childhood epilepsy treated with long-term Anti-Epileptic drugs (AED). Methodology: This cross-sectional study was carried out in the Department of Pediatric Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from March to August 2013. The sample size was one hundred, among these fifty were case (epileptic children who had received anti-epileptic drugs (Carbamazepine and/or Valproic acid) for more than three months) and the rest fifty were control (newly diagnosed epileptic children, who had yet not received antiepileptic drug). Serum copper (Cu) was measured by atomic absorption spectrophotometer. After collecting all the data, analysis has been done by using SPSS and the results are displayed in tables and diagrams. Results: The mean copper level was 1.11±0.32 µg/ml in case group and 0.96±0.20 µg/ml in the control group, which was statistically significant (p<0.05). In this study, epileptic group had a 34% family history of epilepsy, while in control group it was 16% and that was statistically significant (p<0.05). This study also indicated that 78% generalized tonic clonic seizures were in the epileptic group and 70% were in the control group. Serum levels of copper in patients with epilepsy on treatment (particularly with sodium valproate and carbamazepine) were high. Conclusion: The use of one drug or multiple drugs in the treatment of epileptic patients may play a significant role in increasing copper serum levels.